Analisis Pertanggung Jawaban Atas Perseroan Terbatas yang Dinyatakan Pailit - Setyarini, Adelia Tsabita; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
Company law is closely related to the discussion of bankruptcy, where a company can take preventive measures as much as possible so that a company that has been built does not go bankrupt. The urgency in writing this journal is to find out how the bankruptcy of a limited company results in legal consequences, as well as to look more deeply into the responsibilities of directors in a limited company if bankruptcy occurs. In writing this journal, we used an empirical legal writing method, then studied documents to collect data, and used primary legal sources. It can be concluded that legal entities are not automatically owned by limited liability companies. In fact, positive law states that a company's operations will not stop and result in bankruptcy if the right to use and own the company's assets is lost. A person with full authority over all matters of a partnership is the director. With this statement, the obligations and implementation of the company must be carried out en masse by all members of the board of directors. Bankruptcy is due to negligence by the directors or mistakes made by the directors in their duties, therefore there must be a decision. court regarding the actions of directors who must be held accountable and statements regarding the bankruptcy of the company